IMPROVING STUDENTSâ MOTIVATION IN WRITING DESCRIPTIVE TEXTS BY USING THE MIND MAPPING TECHNIQUE - RofiÃ¢Â€Â™i, Agus; Rukmini, Dwi; Hartono, Rudi (English Education Journal, 2014)
This study investigated the Mind Mapping Technique in relation to studentsâ motivation in writing descriptive texts. The problem statements are formulated as follows: (1) what are the problems faced by the students in the process of writing descriptive texts? (2) How is the improvement of the studentsâ motivation in writing descriptive texts through the Mind Mapping Technique? (3) To what extent does the teaching learning process by using the Mind Mapping Technique contribute to the improvement of studentsâ skill in writing descriptive texts? The objectives of this study are: (1) To find out the problems faced by the students in the process of writing descriptive texts, (2) To investigate the improvement of the studentsâ motivation in writing descriptive texts through the Mind Mapping Technique in each cycle, (3) To describe the improvement of studentsâ skill in writing descriptive texts after participating in the teaching learning process by using the Mind Mapping Technique. The design of this research was Classroom Action Research. This research ran the four steps: Planning the action, implementing, observing, and reflecting the action. The results of the study concluded that, the implementation of the Mind Mapping Technique in the teaching of writing descriptive text could develop the ability and improve the motivation.